La monarchia asburgica tra liberalismo e nazionalismo. Note sulla recente letteratura sulla rivoluzione e sul liberalismo - Seiderer, Georg (Ricerche di Storia Politica, 2001)
This review article takes into account recent publications dealing with the history of the 1848/49 Austrian revolution and with post-1849 Austro-German liberalism. The new works on the revolution put particular emphasis on the long-term effects which, in spite of its failure, it has had after 1849. Interest in Austro-German liberalism has intensified in recent years. New interpretations and findings go someway forwards correcting the view - which has dominated until now - of liberalism's "decline" after 1879.